1992
DOI: 10.1117/12.132011
|View full text |Cite
|
Sign up to set email alerts
|

Planar TiO 2 waveguides by the sol-gel process: the relationship of structure to properties

Abstract: Recent works in our laboratories investigated the microstructure of titarna films prepared from a colloidal solution and used as planar waveguides. The transmission electron microscopy including high resolution observations together with waveguide Raman spectroscopy, especially in the very low frequency range, showed a strong influence of the heat-treatment procedure on the films' morphology. In addition, atomic force microscopy provided valuable information on their surface roughness.At lower temperatures(450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…From our results, we can deduce that increasing annealing temperature leads to increasing RMS, refractive index and optical losses. Similar results on the increase of optical losses with the annealing temperature were already reported on sol-gel ZrO 2 [25,32] and TiO 2 [33] films. For the former, Ehrhart et al [32] reported that in order to obtain ZrO 2 thin films with a high refractive index (n = 1.96) and low optical losses (0.29 dB/cm), the best heat-treatment corresponds to an annealing at 400 °C, thus preserving an amorphous phase, while optical losses increase at a temperature of 450 °C when the crystallization into a metastable tetragonal phase appears; Urlacher et al [25] also found that ZrO 2 optical losses increase when the annealing temperature and film crystallinity increase: they obtained 0.8 and 2.5 dB/cm as attenuation coefficients for the amorphous film heat treated at 300 °C and the crystallized film annealed at 600 °C, respectively.…”
Section: Optical Characterizationssupporting
confidence: 87%
See 1 more Smart Citation
“…From our results, we can deduce that increasing annealing temperature leads to increasing RMS, refractive index and optical losses. Similar results on the increase of optical losses with the annealing temperature were already reported on sol-gel ZrO 2 [25,32] and TiO 2 [33] films. For the former, Ehrhart et al [32] reported that in order to obtain ZrO 2 thin films with a high refractive index (n = 1.96) and low optical losses (0.29 dB/cm), the best heat-treatment corresponds to an annealing at 400 °C, thus preserving an amorphous phase, while optical losses increase at a temperature of 450 °C when the crystallization into a metastable tetragonal phase appears; Urlacher et al [25] also found that ZrO 2 optical losses increase when the annealing temperature and film crystallinity increase: they obtained 0.8 and 2.5 dB/cm as attenuation coefficients for the amorphous film heat treated at 300 °C and the crystallized film annealed at 600 °C, respectively.…”
Section: Optical Characterizationssupporting
confidence: 87%
“…For the former, Ehrhart et al [32] reported that in order to obtain ZrO 2 thin films with a high refractive index (n = 1.96) and low optical losses (0.29 dB/cm), the best heat-treatment corresponds to an annealing at 400 °C, thus preserving an amorphous phase, while optical losses increase at a temperature of 450 °C when the crystallization into a metastable tetragonal phase appears; Urlacher et al [25] also found that ZrO 2 optical losses increase when the annealing temperature and film crystallinity increase: they obtained 0.8 and 2.5 dB/cm as attenuation coefficients for the amorphous film heat treated at 300 °C and the crystallized film annealed at 600 °C, respectively. For the latter, Bahtat et al [33] reported that at lower temperatures (450 °C), the films' structure consists of a mixture of amorphous TiO 2 and anatase nanocrystals and its surface is smooth. On the contrary, when increasing the annealing temperature, crystallization increases yielding a higher roughness and the films' waveguiding properties disappear.…”
Section: Optical Characterizationsmentioning
confidence: 99%
“…However, if rutile is the thermodynamically stable phase, anatase may be kinetically stable until about 1000°C, depending on the grain size for example. Such a situation is similar to that of sol-gel thin films where anatase alone has been observed even after annealing at 900°C [11].…”
Section: Discussionsupporting
confidence: 75%
“…For films #l and #2 the width of the anatase main line at 144 cm -1 is broaden relative to that of the bulk crystal (14 cm -1 instead of 7 cm -1 ) [12]. The line width can be related to the mean size of the crystals, which could be of the order of 10 nm as it has been observed for anatase powders [13] and in anatase thin films deposited by the sol-gel method [11].…”
Section: Discussionmentioning
confidence: 73%
“…Purely inorganic solgel derived materials have been explored for a long time [9,10] and such sol-gel materials as SiO 2 and TiO 2 have been investigated for optical applications [11,12]. However, solely inorganic sol-gel derived optical materials can be very porous unless accompanied by high temperature densification.…”
Section: Introductionmentioning
confidence: 99%